PUSAT LAYANAN ANAK AUTIS DI KOTA SURAKARTA DENGAN PENEKANAN TINGKAT KEMANDIRIAN - Ayu Fitri Utami; Suparno Suparno; Leny Pramesti (ARSITEKTURA, 2014)
Abstract:  Child Friendly City Award which was given to the city of Surakarta in 2013, became a separate lashes at the same zeal for the administration to continue to defend the rights of children, autistic children are no exception. Children with autism are children who have developmental disorders of communication, social interaction, and behavior, which have special needs for the sake of the recovery process as well as efforts to become an independent person. In the process leading to independence, there is a structured learning program, which is considered to have the effectiveness of the child in the recovery process, because the process is gradual. These stages contained in the advanced curriculum level of independence that must be done or achieved by the children, who then become a reference in the planning and design decisions Autistic Children Service Center. The purpose of this scheme is to realize a physical container that can accommodate activities to play, learn, and an integrated therapy, which is in accordance with the characteristics and level of independence for children with autism. Design issues are: how to implement advanced curriculum level of independence in children with autism in the planning and design of Autistic Children Service Center in Surakarta, to realize a physical container that is capable of stimulated children more independent in doing activities in an integrated manner. The method used is the method of architectural design. The result is a design Autistic Child Care Center, a physical container to learn, play,  and child therapy, advanced curriculum of the degree of independence, so that stimulated the child and assist the process of recovery and independence. Keywords: Child Autism, Autism Child Care Centre, Level of Independence